La métro-périurbanisation comme nouveau paradigme ? - Émeline Bailly; Hervé Duret (Projets de Paysage)
Stigmatized for a long time, the knowledge of the periurbanized spaces was essentially approached through a series of all-embracing, sometimes ideological presuppositions, ignoring the variety of the urban and social dynamics at work. Though, diversity of periurban spaces appears through a series of urban, functional and landscaped analyses on one hand, lifestyles on the other hand. Moreover, intertwined metropolitan and periurban development processes make possible a different look at the different periurban morphologies, spatially scattered lifestyles, polycentered phenomena and the identity representations. This interdependent dynamics between metropolises and periurban spaces brings us from then on to consider these “metro-periurban” entities as a viable frame for sustainable urban politics adapted to the social and urban realities in presence.